Adaptation and Vertical Integration in the Airline Industry - Forbes, Silke Januszewski; Lederman, Mara (American Economic Review, 2009)
We explore patterns of vertical integration in the US airline industry. Major airlines subcontract portions of their network to regional partners, which may or may not be owned. We investigate if ownership economizes on ex post renegotiation costs. We estimate whether airlines are more likely to use owned regionals on city pairs with adverse weather (which makes adaptation decisions more frequent) and on city pairs that are more integrated into the major's network (which raises the costs of having adaptation decisions resolved suboptimally). Our results suggest a robust empirical relationship between adaptation and vertical integration in this setting. (JEL L14, L22, L24, L93)